Antipyretic and Anti‐inflammatory Effects of Asiaticoside in Lipopolysaccharide‐treated Rat through Up‐regulation of Heme Oxygenase‐1. (12th September 2012) - Wan, JingYuan; Gong, Xia; Jiang, Rong; Zhang, Zhuo; Zhang, Li
<x xml:space="preserve">Abstract</x> Asiaticoside (AS), a triterpenoid isolated from Centella asiatica, has been found to exhibit antioxidant and anti‐inflammatory activities in several experimental animal models. However, the underlying mechanisms remain elusive. In this study, we provide experimental evidences that AS dose‐dependently inhibited lipopolysaccharide (LPS)‐induced fever and inflammatory response, including serum tumor necrosis factor (TNF)‐α and interleukin (IL)‐6 production, liver myeloperoxidase (MPO) activity, brain cyclooxygenase‐2 (COX‐2) protein expression and prostaglandin E2 (PGE2) production. Interestingly, AS increased serum IL‐10 level, liver heme oxygenase‐1 (HO‐1) protein expression and activity. Furthermore, we found that the suppressive effects of AS on LPS‐induced fever and inflammation were reversed by pretreatment with ZnPPIX, a HO‐1 activity inhibitor. In summary, our results suggest that AS has the antipyretic and anti‐inflammatory effects in LPS‐treated rat. These effects could be associated with the inhibition of pro‐inflammatory mediators, including TNF‐α and IL‐6 levels, COX‐2 expression and PGE2 production, as well as MPO activity, which might be mediated by the up‐regulation of HO‐1. Copyright © 2012 John Wiley & Sons, Ltd.